Functional outcome after surgical decompression of lumbar canal stenosis - Ravikumar Biradar; Mohammed Ateeq (Al Ameen Medical College, 2022)
Background: Low back pain with or without leg pain, sometimes associated with paraesthesia is a common occurrence in the community. Apart from lumbago, spondylosis and herniated disc, which usually cause low back pain, associated leg pain and paraesthesia. Also the stenosis of lumbar canal with degenerative changes is very commonly found in Middle and old aged individuals, responsible for considerable disability. It is said that decompression of stenosed canal gives relief to a great extent. Hence to know the outcome of pain relief, problems associated with procedure and the patient's satisfaction post surgically. Aims and Objectives: To evaluate outcome of the procedure and to understand the problems related to the procedure. Methods and Observations:20 patients of Lumbar spinal stenosis who visited Al-Ameen Medical College Hospital, Vijayapura out of which 8 patients with primary canal stenosis, 8 others with secondary canal stenosis and 4 patients with degenerative listhesis with stenosis were subjected for laminectomy, after the meticulous preoperative examination and MRI imaging. Postoperative observations with reference to Low back pain, leg pain, and claudication, walking distance, neurological status and Activities of daily living were drawn. 85% of them had combined Low back pain and Leg pain, severity scale was high in mixed stenosis than pure canal stenosis. Neurological claudication was found to be a hallmark presentation. Restoration of walking ability is one of the most diagnostic functional parameter. Neurological recovery was good to the extent of relieving paraesthesia.Results:80% of the study rated as excellent with the mean Swiss spinal stenosis score being 12.22%; 20% rated as good with mean score being 21.19%. The mean age of presentation 49.4% and mean duration of symptoms was 11.7 months. Conclusion: Surgical decompression addresses dramatically the morbid symptoms like neurological claudication and radicular pain and improved the walking ability. The problems and complications are the least, insignificant and inconsequential.